Edukasi Kepatuhan Konsumsi Tablet Tambah Darah sebagai Upaya Pencegahan Anemia pada Remaja di Wilayah Kerja Puskesmas Mangkung - Apriani, Lia; Fitria, Baiq; Budiatin, Farida Susila; Maesarah, Maesarah; Martina, Teti; Indra Wiguna, Reza (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Adolescent anemia remains a significant public health problem in Indonesia, primarily caused by inadequate iron intake, limited nutritional literacy, and low adherence to iron supplementation programs. Although both male and female adolescents are affected, females are at higher risk due to physiological factors. This community service program aimed to improve adolescents’ knowledge, understanding, and initial attitudes toward Iron-Folic Acid (IFA) supplementation as a strategy for anemia prevention. The program was conducted at Salman Al-Farisi Islamic Boarding School in Central Lombok, involving both male and female adolescents. The intervention consisted of a single-session participatory education approach, including interactive lectures, group discussions, demonstrations of proper IFA consumption, and the use of educational media such as posters and leaflets. The results demonstrated a significant improvement in knowledge, with the proportion of participants with good knowledge increasing from 20% to 70%, and poor knowledge decreasing from 45% to 5%. Participants also showed more positive initial attitudes and greater openness toward IFA consumption. However, due to the one-time nature of the intervention, long-term adherence could not be evaluated. Therefore, the primary outcome of this program is an increased level of behavioral readiness, serving as a foundation for long-term behavior change. In conclusion, this educational intervention successfully strengthened adolescents’ cognitive and affective foundations for anemia prevention. Continuous education and routine monitoring are recommended to promote sustained adherence to IFA supplementation programs.